An apparatus for the determination of speeds of sound in fluids - Gedanitz, Holger; Dávila, María J.; Baumhögger, Elmar; Span, Roland (The Journal of Chemical Thermodynamics)

Social Search: Exploring and Searching Social Architectures in Digital Networks - Trier, Matthias; Bobrik, Annette (IEEE Internet Computing)

Enabling social media content quality assurance using social network analysis - Sanmateu, Maria-Amparo; Trier, Matthias; Lienicke, Andreas; Rederer, Andreas (9th International Conference On Innovative Internet Community Systems I2CS 2010)

Content-based Community Detection in Social Corpora - Bobrik, Annette; Trier, Matthias (Proceedings Wirtschaftsinformatik)

Odp2cp – ein rapid E-Learning Ansatz zur einfachen Produktion Scorm-konformer Lerninhalte - Trier, Matthias; Herzog, Michael; Möller, Daniel (Proceedings Wirtschaftsinformatik)

Cooperation and coding framework - Biermann, Thorsten; Polgar, Zsolt Alfred; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Combining for cooperative WLANs-a reality check based on prototype measurements - Valentin, Stefan; Woldegebreal, Dereje H; Volkhausen, Tobias; Karl, Holger (Communications Workshops, 2009. ICC Workshops 2009. IEEE International Conference on)

Improving network coded cooperation by soft information - Volkhausen, Tobias; Woldegebreal, Dereje H; Karl, Holger (Sensor, Mesh and Ad Hoc Communications and Networks Workshops, 2009. SECON Workshops' 09. 6th Annual IEEE Communications Society Conference on)

On the usefulness of fuzzy sets in data mining - Hüllermeier, Eyke (Views on Fuzzy Sets and Systems from Different Perspectives: Philosophy and Logic, Criticisms and Applications)

Statistics-based ID management for load balancing in structured P2P networks - Warneke, Daniel; Dannewitz, Christian (2009 IEEE 34th Conference on Local Computer Networks)

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, Guido (physica status solidi (c))

Vacancy clusters created via room temperature irradiation in 6H-SiC - Scholle, A.; Greulich-Weber, S.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physica B: Condensed Matter)

Decision tree and instance-based learning for label ranking - Cheng, W.; Hühn, J.; Hüllermeier, Eyke (in Proceedings ICML-2009, 26th International Conference on Machine Learning, Montreal, Canada)

Binary decomposition methods for multipartite ranking - Fürnkranz, J.; Hüllermeier, Eyke; Vanderlooy, S. (In Proceedings ECML/PKDD-2009, European Conference on Machine Learning and Principles and Knowledge Discovery in Databases, Bled Sloveniaery in Databases, Bled, Slovenia)

A new instance-based label ranking approach using the Mallows model. In Advances in Neural Networks - Cheng, W.; Hüllermeier, Eyke (in Proceedings 6th International Symposium on Neural Networks, Wuhan, China)

A Multithreaded Framework for Sequential Monte Carlo Methods on CPU/FPGA Platforms - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Towards Models for Many-Cores: The Case for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the Workshop on Many-Cores, International Conference on Architecture of Computing Systems (ARCS))

ARMLang: A Language and Compiler for Programming Reconfigurable Mesh Many-Cores - Giefers, Heiner; Platzner, Marco (Reconfigurable Architectures Workshop (RAW), Proceedings of the International Parallel and Distributed Processing Symposium)

Cooperative Multithreading in Dynamically Reconfigurable Systems - Lübbers, Enno; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

Program-driven Fine-grained Power Management for the Reconfigurable Mesh - Giefers, Heiner; Platzner, Marco (Proceedings of the 19th International Workshop on Field Programmable Logic and Applications (FPL))

An adaptive Sequential Monte Carlo framework with runtime HW/SW repartitioning - Happe, Markus; Lübbers, Enno; Platzner, Marco (Proceedings of the 2009 International Conference on Field-Programmable Technology (FPT))

Proof-carrying Hardware: Towards Runtime Verification of Reconfigurable Modules - Drzevitzky, Stephanie; Kastens, Uwe; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))

Water adsorption on the α-Al2O3(0001) surface - Thissen, P.; Grundmeier, G.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Rare-earth defect pairs in GaN: LDA+U calculations - Sanna, Simone; Schmidt, Wolf Gero; Frauenheim, Th.; Gerstmann, Uwe (Physical Review B)

Adsorption structure of cyclopentene on InP(001)(2×4) - Passmann, Regina; Favero, Priscila; Schmidt, Wolf Gero; Miotto, Ronei; Braun, Walter; Richter, Wolfgang; Kneissl, Michael; Esser, Norbert; Vogt, Patrick (Physical Review B)

Role of Dihydrogen Bonds for the Stabilization of Self-Assembled Molecular Nanostructures - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Structure of Si(111)-In Nanowires Determined from the Midinfrared Optical Response - Chandola, S.; Hinrichs, K.; Gensch, M.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Fleischer, K.; McGilp, J. F. (Physical Review Letters)

Chainlike Au−O Structures on Au(110)-(1 × r) Surfaces Calculated from First Principles - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Glutamic acid adsorbed on Ag(110): direct and indirect molecular interactions - Blankenburg, S; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Water adsorption on hydrogenated Si(111) surfaces - Lange, B.; Posner, R.; Pohl, K.; Thierfelder, C.; Grundmeier, Guido; Blankenburg, S.; Schmidt, Wolf Gero (Surface Science)

First-principles calculations of clean Au(110) surfaces and chemisorption of atomic oxygen - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

QUANTUM ESPRESSO: a modular and open-source software project for quantum simulations of materials - Giannozzi, Paolo; Baroni, Stefano; Bonini, Nicola; Calandra, Matteo; Car, Roberto; Cavazzoni, Carlo; Ceresoli, Davide; Chiarotti, Guido L; Cococcioni, Matteo; Dabo, Ismaila; Dal Corso, Andrea; de Gironcoli, Stefano; et al. (Journal of Physics: Condensed Matter)

Spin-Coupling in Heavily Nitrogen-Doped 4H-SiC - Savchenko, D.V.; Pöppl, Andreas; Kalabukhova, Ekaterina N.; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
EPR and ESE in nitrogen doped 4H- and 6H-SiC show besides the well known triplet lines of 14N on quasi-cubic (Nc,k) and hexagonal (Nc,h) sites additional lines (Nx) of comparatively low intensity providing half the hf splitting of Nc,k. Frequently re-interpreted as spin-forbid¬den lines, arising from Nc,k pairs and triads or resulting from hopping conductivity, only re¬cent¬ly the theoretical calculation of the corresponding g-tensors lead to a tentative model of distant NC donor pairs on inequivalent lattice sites which are coupled to S = 1 assuming a fine-struc¬ture splitting too small to be observed in the EPR and ESE experiments. In this work, we pre¬sent ESE nutation measurements confirming S = 1 for the Nx center. Analysing the nutation frequencies in comparison with that of the Nc,k (S = 1/2) spectrum as well as the line width of ESE and EPR spectra we obtain a rough estimate between 5104 cm-1 and 50104 cm-1 for the fine-structure splitting demonstrating efficient spin-coupling between nitrogen donors in 4H-SiC.

Vieweg, Klaus, Il pensiero della libertà, Pisa 2007 - Ficara, Elena (Iride)

Nuzzo, Angelica, Kant and the Unity of Reason, Purdue University Press, Indiana 2005 - Ficara, Elena (Fichte-Studien)

Vieweg, Klaus, Skepsis und Freiheit, München 2007 - Ficara, Elena (Hegel-Studien)

Nichts, Negation, Nihilismus. Die Europäische Moderne als Erkenntnis und Erfahrung des Nichts - Ficara, Elena (Fenomenologia e società)

Die Begründung der Philosophie im Deutschen Idealismus - Ficara, Elena (Rivista di storia della filosofia)

Hegels Kampfbegriff zwischen Logik und Politik - Ficara, Elena (Hegel Jahrbuch)

‚Transzendental‘ bei Kant und Fichte - Ficara, Elena (Fichte-Studien)

Semi-Digital Interleaved PFC Control with Optimized Light Load Efficiency - Grote, Tobias; Figge, FHeiko; Fröhleke, Norbert; Beulen, Winfried; Schafmeister, Frank; Ide, Peter; Böcker, Joachim (Proc. 24th IEEE Applied Power Electronics Conference (APEC))

Adaptive Digital Slope Compensation for Peak Current Mode Control - Grote, Tobias; Schafmeister, Frank; Figge, Heiko; Fröhleke, Norbert; Ide, Peter; Böcker, Joachim (Proc. IEEE Energy Conversion Congress and Exposition (ECCE))

Verfahren zur Nutzung des ausgangsseitigen Blindstromes eines indirekten dreiphasen-Matrixkonverters zur Erzeugung von Eingangsblindstrom - Schafmeister, Frank; Kolar, Johann

Energy transfer via linear doubly-fed motor in different operating modes - Schneider, T.; Schulz, B.; Henke, C.; Witting, K.; Steenken, D.; Böcker, Joachim (2009 IEEE International Electric Machines and Drives Conference)

Optimal design of motor and gear for drives with high acceleration and load torque - Grotstollen, H. (2009 IEEE International Electric Machines and Drives Conference)

Optimal energy management for a hybrid energy storage system combining batteries and double layer capacitors - Romaus, C.; Böcker, Joachim; Witting, K.; Seifried, A.; Znamenshchykov, O. (2009 IEEE Energy Conversion Congress and Exposition)